Sporto treneriu suvokiamos savireguliacijos vertinimas - Gražulis, D.; Sabaliauskas, S.; Žilinskiene, N.; Kaukenas, T. (Sporto Mokslas-Sport Science, 2022)
Self-regulation is the ability to design, implement and flexibly maintain planned behaviors to achieve goals. Self-regulated learning (SRL) is the way in which an individual, athlete or sports coach optimizes the conditions, manages himself and his effort or performance and the whole of the sport practice by performing tasks. In order to investigate coaches` self-regulation, it was relevant to adapt this questionnaire to the Lithuanian population of coaches, and therefore the aim of the present study was to assess the self-regulation perceived by sports coaches. The Self-Regulation Questionnaire (SRQ) was used to assess coaches` self-regulation. It was designed to assess self-regulation processes in the development, implementation and flexible adaptation of planned behaviors in order to achieve goals based on personal self-reflection. The self-regulation model selected consists of seven subscales, each with 9 statements (63 statements in total). The study involved 43 team and individual sport coaches (15 women, 28 men) representing 20 sports. The age of the participants ranged from 28 to 67 years (mean 47.6 ± 9.71 years) and the coaching experience ranged from 1 to 45 years (mean 16.97 ± 10.5 years). The results of the study showed that the coaches` self-regulation was at a moderate level of 237.53 ± 20.81 (95 PI [231.13-243.96]) when assessed according to the SRQ authors` methodology. The descriptive statistics of the subscales showed that coaches scored lowest on "Evaluating information and comparing it with norms", and highest on "Formulating a plan" and "Evaluating the effectiveness of the plan". When analyzing the results by gender, it was found that women scored higher on self-regulation, but a statistically significant difference was found in the subscale "Searching for options". No statistically significant differences were found when analyzing coaches` self-regulation in terms of age and coaching experience. The aim of the study was to test a diagnostic instrument developed by other researchers to assess coaches` perceived self-regulatory abilities. This study is important because it was adapted to the context of Lithuanian sports coaches and the Lithuanian version of the scale was evaluated with psychometric measurements. The study is also particularly significant because it is one of the first time that the SRQ has been used to investigate the self-regulation abilities of Lithuanian sports coaches. The psychometric parameters of the Lithuanian SRQ scale confirmed the validity of the scale for data analysis, but in the future the study should be conducted with a larger number of subjects (larger sample).